1107 PLASMA CIRCULATING TRANSTHYRETIN FORMS IN PATIENTS WITH WILD TYPE TRANSTHYRETIN CARDIAC AMYLOIDOSIS. (15th December 2022) - Castiglione, Vincenzo; Sanguinetti, Chiara; Panichella, Giorgia; Minniti, Marianna; Caponi, Laura; Aimo, Alberto; Paolicchi, Aldo; Emdin, Michele; Vergaro, Giuseppe; Franzini, Maria
Abstract: Background and aims: Wild type transthyretin (TTR) cardiac amyloidosis (ATTRwt-CA) is caused by the misfolding, aggregation and tissue deposition of native TTR, leading to cardiac structural remodeling. In the last decade, the validation of non-invasive diagnostic approaches and the development of novel therapeutic options targeting the amyloidogenic cascade, such as the TTR stabilizer tafamidis, have dramatically changed the epidemiology and the prognosis of the disease. Nonetheless, the basic pathophysiological mechanisms underlying TTR misfolding and aggregation are still poorly understood. We aimed to characterize circulating TTR forms in plasma samples of ATTRwt-CA patients before and after treatment with tafamidis through a native electrophoretic method. Methods: Plasma samples from 6 male patients with ATTRwt amyloidosis (median age 82 years, IQR 80-83), collected before (T0) and during tafamidis treatment, and from 6 healthy controls were collected. Plasma samples were separated on a native 4–20% Tris-Gly polyacrylamide gel. Western blot analysis was performed with anti-TTR or anti-retinol-binding protein (RBP) antibodies. Proteins were detected by Clarity ECL substrate. Results: Circulating TTR forms were qualitatively similar between ATTRwt-CA patients at T0 and controls. In both groups, the most represented forms were TTR dimers or trimers (∼37-50 kDa), TTR tetramers complexed with RBP in 1:1 ratio (∼80 kDa) or 1:2 ratio (∼100 kDa), and high molecular weight (MW) aggregates (>150 kDa). Neither TTR monomers nor tetramers could be detected. RBP protein was detectable in association with TTR tetramers and some of the higher MW fractions (∼150 kDa, >250 kDa). Following tafamidis treatment, all ATTRwt-CA patients displayed a progressive increase of the intensity of the band corresponding to TTR-RBP complexes, in agreement with the a stabilizing action on TTR tetramers. Interestingly, dimers and trimers, detectable at T0, were progressively lost during tafamidis treatment. Conclusions: TTR tetramer exists only complexed with RBP and in equilibrium with low and high MW forms, without apparent qualitative differences between ATTR-CA and healthy controls. Tafamidis increases circulating TTR tetramers complexed with RBP. Evaluation of TTR isoform may prove useful as a circulating biomarker for the assessment of response to treatment in patients with ATTRwt-CA. Figure. Electrophoretic analysis of circulating TTR forms. The figure shows the distribution of the different circulating forms of transthyretin (TTR) in a patient with wild type TTR cardiac amyloidosis prior to initiation of tafamidis therapy ("Pre" column) and at 4 months, 5 months, and 1 year follow-up (columns "4m", "5m" and "1a", respectively) from the beginning of the therapy. The two "C" columns on the right show the distribution of circulating TTR forms in a healthy control. The "TTR" column shows the electrophoretic run of the commercially available purified TTR tetramer.